2022
DOI: 10.1097/wnr.0000000000001823
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted interhemispheric functional connectivity in primary angle-closure glaucoma: a functional MRI study: voxel-mirrored homotopic connectivity in primary angle-closure glaucoma patients

Abstract: The purpose of the study is to use the voxel-mirrored homotopic connectivity (VMHC) technique to explore the pattern of the interhemispheric functional connectivity in patients with primary angle-closure glaucoma (PACG). The interhemispheric functional connectivity was compared between 31 individuals with PACG and 31 healthy controls closely matched with sex, age, and educational level using the VMHC technique. Significant differences in VMHC between two groups were selected to be classification features for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Results showed a notable decline in DC values within the DMN among PACG patients, signaling reduced functional connectivity in this network [27]. Similarly, both Yan et al and Yong et al observed disrupted FC between brain hemispheres during resting-state in PACG patients, with impairment observed within the DMN, which is a high-level visual area [28,29]. However, the exact relationship between alterations in the DMN and PACG still requires further investigation.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Results showed a notable decline in DC values within the DMN among PACG patients, signaling reduced functional connectivity in this network [27]. Similarly, both Yan et al and Yong et al observed disrupted FC between brain hemispheres during resting-state in PACG patients, with impairment observed within the DMN, which is a high-level visual area [28,29]. However, the exact relationship between alterations in the DMN and PACG still requires further investigation.…”
Section: Introductionmentioning
confidence: 84%
“…and Yong et al . observed disrupted FC between brain hemispheres during resting-state in PACG patients, with impairment observed within the DMN, which is a high-level visual area [28,29]. However, the exact relationship between alterations in the DMN and PACG still requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…As a functional integration approach, VMHC assesses the brain as an integrated network, which differs from functional segregation indices (such as ALFF), may be useful to identify more abnormalities and explain the neural mechanism of diseases from a distinct perspective. Researches have demonstrated that VMHC is useful in exploring the interhemispheric functional connectivity in various neurological disorders and ophthalmic diseases, such as Parkinson's disease, glaucoma, diabetic nephropathy complicated by retinopathy, thyroid-associated ophthalmopathy, and amblyopia (Wang et al, 2020;Chen et al, 2021;Peng et al, 2021;Tong et al, 2022;Zhang et al, 2022). A recent study also demonstrated interhemispheric homotopic connectivity alterations in the cerebellum in CE patients (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 98%
“…Wang et al 9 found extensive abnormal rs-FC between the thalamus and visual and extravisual brain areas. Tong et al 10 demonstrated that there is disturbed interhemispheric resting-state functional connectivity in the vision-related brain areas of individuals with PACG. Besides, our research team previously observed that patients with PACG exhibited brain dysfunction in various areas, and displayed distinct spatial variations in both proximal and distal functional connection density (FCD) 11 .…”
Section: Introductionmentioning
confidence: 99%